Comedy comedy comedy drama : a memoir - Odenkirk, Bob, 1962- (Random House, 2022)
"Bob Odenkirk's career is inexplicable. And yet he will try like hell to explain it here, because that is what memoirs are for. Charting a "Homeric" decades-long "Odyssey" from his origins in the seedy comedy clubs of Chicago all the way to a dramatic career that is baffling to his friends, it's almost like there are two or three Bob Odenkirks...but there is just one and one is enough, frankly. Bob embraced a life in comedy after a chance meeting with Second City's legendary Del Close, which eventually led to a job as a writer at SNL. As he weathered the beast that is live comedy, he stashed away the secrets of sketch writing-employing them in the immortal "Motivational Speaker" sketch for his friend Chris Farley, honing them on The Ben Stiller Show, and perfecting them on Mr. Show With Bob and David, which inspired an entire generation of comedy writers and stars. Then his career met the hope-dashing machine that is Hollywood development. But when all hope was lost for the umpteenth time, Bob was more astonished than anyone to find himself on Breaking Bad. His embrace of this strange new world of dramatic acting led him to working with Steven Spielberg, Alexander Payne, and Greta Gerwig, until finally re-re-inventing himself as a bona-fide worldwide action star for reasons that even he does not fully grasp! Read this and do your own psychoanalysis-it's fun!"--